Literature Review: Cost Effectiveness Analysis Xpert MTB/RIF dibandingkan dengan Sputum Smear Microscopy untuk Diagnosis Tuberkulosis di Indonesia - Putri, Linda Wahyuni; Hartono, Budi (Indonesian of Health Information Management Journal (INOHIM), 2023)
Abstract Indonesia is the third most TB-prevalent country in the world after India and China. Sputum Smear Microscopy (SSM) is the most commonly used Tuberculosis test in developing countries due to its relatively low unit cost per test but low sensitivity. The World Health Organization recommends using Xpert MTB/RIF as a TB test because it has higher sensitivity and specificity and a shorter time to obtain results. This paper evaluates the cost-effectiveness analysis of Xpert MTB/RIF and Sputum Smear Microscopy in Indonesia. The search for scientific articles was conducted by keyword search through Google Scholar, PubMed, and Elsevier. The keywords used were related to "Cost-Effectiveness Analysis", "Xpert MTB/RIF and Sputum Smear Microscopy", and "Cost Effectiveness Analysis Xpert MTB/RIF and Sputum Smear". Articles identified through database searches were 1,040 articles with a research period of 2016 - 2023. They have obtained nine articles that have the most relevant topics. The results of the analysis of the nine articles show that when viewed from the overall costs required for TB suspect / TB-positive patients to obtain a cure, including the cost of follow-up tests, costs incurred due to treatment, and costs due to treatment in the hospital, Xpert MTB/RIF is considered more cost-effective than SSM. As one of the ten most dangerous infectious diseases in the world, it is hoped that the government's health insurance efforts related to TB case management can reduce the spread and mortality rate of TB in Indonesia.Keywords: Cost-Effectiveness Analysis, Tuberculosis, Sputum Smear Microscopy, Xpert MTB/RIF Abstrak Indonesia menempati posisi ketiga sebagai negara dengan prevalensi TB terbanyak di dunia setelah India dan China.Sputum Smear Microscopy (SSM) merupakan tes Tuberkulosis yang paling sering digunakan di negara berkembang karena unit cost per tes yang relatif murah, tetapi memiliki sensitivitas yang rendah. World Health Organization merekomendasikan penggunaan Xpert MTB/RIF sebagai tes TB karena memiliki sensitivitas dan spesifisitas yang lebih tinggi serta waktu perolehan hasil yang lebih singkat. Karya tulis ini bertujuan untuk mengevaluasi cost effectiveness analysis terhadap pemeriksaan Xpert MTB/RIF dan Sputum Smear Microscopy di Indonesia. Pencarian artikel ilmiah dilakukan dengan pencarian kata kunci melalui Google Scholar, PubMed, dan Elsevier. Kata kunci yang digunakan berhubungan dengan “Cost Effectiveness Analysis”, “Xpert MTB/RIF dan Sputum Smear Microscopy”, “Cost Effectiveness Analysis Xpert MTB/RIF and Sputum Smear”. Artikel yang teridentifikasi melalui pencarian database sebanyak 1.040 artikel dengan rentang waktu penelitian 2016 – 2023. Diperoleh 9 artikel yang memiliki topik yang paling relevan. Hasil analisis terhadap 9 artikel menunjukkan bahwa jika ditinjau dari keseluruhan biaya yang diperlukan pasien suspect TB/TB positif untuk memperoleh kesembuhan diantaranya seperti: biaya test lanjutan; biaya yang ditimbulkan karena perawatan; dan biaya akibat pengobatan di rumah sakit, maka Xpert MTB/RIF dinilai lebih cost effective dibandingkan SSM. Sebagai salah satu penyakit yang masuk ke dalam sepuluh penyakit menular berbahaya di dunia, diharapkan upaya jaminan kesehatan dari pemerintah terkait penanggulangan kasus TB dapat menekan angka penyebaran dan kematian akibat TB di Indonesia.Kata Kunci: Cost Effectiveness Analysis, Tuberkulosis, Sputum Smear Microscopy, Xpert MTB/RIF